Eight weeks of heavy strength training increases hemoglobin mass and VO2peak in well-trained to elite female and male rowers - Lundby, C.; Mazza, O.; Nielsen, J.; Haubro, M.; Kvorning, T.; Ørtenblad, N.; Gejl, K. D. (Journal of Applied Physiology, 2024)
O2-transport and endurance exercise performance are greatly influenced by hemoglobin mass (Hbmass), which largely depends on lean body mass (LBM). This study investigated the effects of 8 wk with three weekly sessions of conventional (3-SET: 3 × 10 reps) or high-volume strength training (10-SET: 5-10 × 10 reps) on LBM, Hbmass, muscle strength, and exercise performance in female and male rowers. Hematological parameters were obtained through CO rebreathing and body composition by dual-energy X-ray absorptiometry (DEXA) scans before and after the training period. Concomitantly, VO2peak was determined during 2-km ergometer rowing and muscle strength by isometric midthigh pull. There were no differences in training responses between groups for any of the parameters. Pooled data revealed overall increments for Hbmass (10-SET: 882 ± 199 g to 897 ± 213 g; 3-SET: 936 ± 245 g to 962 ± 247 g, P = 0.02) and VO2peak (10-SET: 4.3 ± 1.0 to 4.4 ± 0.9 L·min-1; 3-SET: 4.5 ± 0.9 to 4.6 ± 0.9 L·min-1, P = 0.03), whereas LBM remained unchanged (10-SET: 58.7 ± 10.5 to 58.7 ± 10.1 kg; 3-SET: 64.1 ± 10.8 to 64.5 ± 10.6 kg, P = 0.42). Maximal isometric midthigh pull strength increased (10-SET: 224 ± 47 kg to 237 ± 55 kg; 3-SET: 256 ± 77 kg to 281 ± 83 kg, P = 0.001). Strong associations were observed between LBM and Hbmass and VO2peak (r2 = 0.88-0.90), entailing sex differences in Hbmass and VO2peak. Normalizing VO2peak to LBM reduced the sex difference to ~10%, aligning with the sex difference in Hbmass·LBM-1. Strength training successfully increased Hbmass and VO2peak in elite female and male rowers, without an additional effect from increased training volume. Moreover, sex differences in VO2peak were mainly explained by differences in LBM, but likely also by differences in Hbmass·LBM-1.